(untitled) (ENTHYMEMA, 2020)
This essay claims that the “character” is a narratological structure and that since the prehistory when there are stories there are always characters. Thanks to character men try to represent mimetically the complexity of human experience. But the way to conceive the characters has changed during the centuries. In the last decades for example we often encounter characters who are elusive, who escape the grip of narrator (and of reader). This new kind of character is not expression of a nihilistic purpose (that is the impossibility to know reality), but it testifies to a vision of reality adverse to the vision today prevailing. That is to say that these writers maintain that if we want know reality better we have to respect its complexity, its opaqueness, its silences, its resistance to our will to knowledge, our will to truth.